Comportamento contraceptivo e decisão reprodutiva de mulheres no contexto do HIV - Lima, Reângela Cíntia Rodrigues de Oliveira (2023)
Women living with HIV face many challenges related to their sexuality, reproduction, contraception and motherhood. The inconsistent use of contraceptives and unsafe sexual practices increase the chances of sexual and vertical HIV transmission, unplanned pregnancies, pregnancy complications and unsafe abortions. Thus, this study had the general objective of analyzing contraceptive practices and the reproductive desire of women living with HIV. Cross-sectional analytical research, carried out with 165 women with HIV through face-to-face interviews with a form to identify sociodemographic, clinical, sexual, reproductive data and decision-making power in the relationship; and a Questionnaire about values and beliefs about sexuality, motherhood and abortion with five domains (pleasure, affectivity, reproduction, motherhood, abortion). The outcome variables were: desire for pregnancy; contraceptive use and partner control. Data were analyzed using the Stata 13 software. Sociodemographic, clinical, sexual and reproductive characteristics were associated with the outcomes, using the χ2 test, p<0.05, prevalence ratio, 95% accuracy of the effect and bivariate analysis in the data with p<0.10. Of the total, 84 (50.9%) of the women were brown, with a mean age of 29.6 years and 120 (72.7%) had ≤ 9 years of education. Most of them 88 (53.3%) do not have children and 98 (60.1%) live with a serodiscordant partner. In sexual aspects, 103 (62.4%) of the women could not choose to use a condom during sexual intercourse and 67 (40.6%) the partner controls condom use. Regarding reproductive aspects, 57 (34.5%) of the women would have children just to please their partners and 109 (66.1%) talked about reproductive planning. As for the use of contraceptives, 102 (61.8%) of the women did not use contraceptives. Regarding health care, 115 (69.7%) assured that the health professional does not inform about pregnancy and vertical transmission and were emphatic in stating that they did not receive guidance on contraceptives 88 (53.4%). Most women with reproductive desire were married, had other children (p=0.042), used antiretrovirals, partners got what they wanted in the relationship (p=0.019) and had professional guidance (p 0.001). Among women who used contraceptives, there was an association with time studying (p 0.001); in choosing and using condoms (p=0.011), among those who discussed planning (p 0.001) and among those who reported that the partner has more control over important decisions that affect the relationship (63.6%), being associated with these findings the family income >1 minimum wage (p=0.001), the power to refuse to have sexual intercourse without a condom (p=0.049), the partner's control over the use or not of condoms (p=0.013), if the partner gets what he wants (p=0.040), if he felt forced to have sex (p 0.001), with monitoring by a health professional (p=0.028) and those who had already discussed planning with the partner (p=0.009) . It is concluded that among women with HIV, the minority uses contraceptive methods and has a desire for pregnancy after diagnosis of the infection and that the partners have more control in important decisions that affect the relationship, including issues related to sexual health and reproductive desire.